2022
DOI: 10.3390/applmicrobiol2010008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Escherichia coli from Water and Food Sold on the Streets of Maputo: Molecular Typing, Virulence Genes, and Antibiotic Resistance

Abstract: The aim of this study was to investigate the pathogenic potential and antibiotic resistance of 59 Escherichia coli isolates from ready-to-eat (RTE) street food (n = 31) and drinking water (n = 28) sold in the city of Maputo, Mozambique. The isolates were characterized by XbaI subtyping analysis via pulsed field gel electrophoresis. Multiplex PCRs were performed targeting five virulence genes (stx, lt, st, astA, and eae) and three groups of antibiotic-resistant genes, namely ß-lactamases (extended-spectrum ß-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The MOX gene was only detected in raw water 1 in NW-E. DHA was also absent in NW-C DWPF, but it was detected in raw than treated water of NW-E DWPF. Although not extensively featured in environmental studies, these genes have been reported in various niches [ 13 , 52 – 54 ]. pAmpCs are widespread in various niches where their effects may be undesirable for human health [ 51 ] and they are underexplored in the DWPFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MOX gene was only detected in raw water 1 in NW-E. DHA was also absent in NW-C DWPF, but it was detected in raw than treated water of NW-E DWPF. Although not extensively featured in environmental studies, these genes have been reported in various niches [ 13 , 52 – 54 ]. pAmpCs are widespread in various niches where their effects may be undesirable for human health [ 51 ] and they are underexplored in the DWPFs.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic environments are important vectors of antibiotic resistance, which provide favourable conditions for bacterial growth and spread antibiotic resistance genes (ARGs) via horizontal gene transfer to other species [ 10 , 11 ]. However, in South Africa, antibiotic resistance is not monitored and regulated in aquatic environments despite being reported in drinking water [ 12 , 13 ]. Furthermore, studies addressing antibiotic resistance in drinking water focus on detecting ARGs and not so much on quantifying ARGs and antibiotic residues.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the high prevalence of antibiotic resistance findings in this study is likely due to multiple factors, including unrestricted and inappropriate use of antibiotics through self-medication, the sale of antibiotics in informal markets [ 35 , 36 ], cross-contamination through environmental and food sources [ 33 , 37 , 38 ] and the use of antibiotics in animal husbandry without proper guidance from healthcare professionals [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…When associated with poor hygiene practices by handlers and poor hygienic conditions of the exposure environment, ready-to-eat (RTE) street food presents a potential risk of transmission of staphylococcal strains [31][32][33][34][35][36]. In Maputo, Mozambique, street foods are sold in environments with poor sanitation conditions and lack of potable water, which increases the risk of street food contamination [33,34,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…When associated with poor hygiene practices by handlers and poor hygienic conditions of the exposure environment, ready-to-eat (RTE) street food presents a potential risk of transmission of staphylococcal strains [31][32][33][34][35][36]. In Maputo, Mozambique, street foods are sold in environments with poor sanitation conditions and lack of potable water, which increases the risk of street food contamination [33,34,37,38]. This study is a follow-up to previous research by [31], and aims to evaluate the antimicrobial resistance profile and the occurrence of both virulence-and antibiotic-resistance genes in 66 coagulase-positive and coagulase-negative Staphylococcus isolates previously recovered from RTE foods sold on the streets of Maputo, Mozambique.…”
Section: Introductionmentioning
confidence: 99%